Secretomes derived from osteogenically differentiated jaw periosteal cells inhibit phenotypic and functional maturation of CD14+ monocyte-derived dendritic cells - Cen, Wanjing; Umrath, Felix; Salgado, António José; Reinert, Siegmar; Alexander, Dorothea (Frontiers in Immunology, 2023)
The jaw periosteal tissue is generally recognized as a suitable source for the isolation of mesenchymal stem cells (MSCs). In previous studies we showed evidence that two- and three-dimensionally cultured jaw periosteum-derived MSCs (JPCs) are able to induce a more immature phenotype of dendritic cells (DCs). To further expand our knowledge of JPCs' immunoregulative function, we investigated the effects of JPC secretomes derived from undifferentiated (CO) or osteogenically differentiated cells (treated with or without dexamethasone: OB+/-D) on CD14+ monocyte-derived DCs (MoDCs). We detected a remarkably reduced formation of MoDC homotypic clusters under the influence of secretomes from osteogenically induced JPCs. Further, significantly decreased numbers of CD83+ cells, up-regulated CD209 and down-regulated CD80, CD86 and CD197 expression levels were detected on the surface of MoDCs. Whereas secretomes from JPCs osteogenically stimulated with dexamethasone significantly enhanced FITC-dextran uptake capacity of MoDCs, the increase by secretomes of JPCs treated without dexamethasone did not reach significance. The analysis of mixed lymphocyte reactions revealed that OB+/-D secretomes were able to significantly reduce the numbers of proliferating CD14- peripheral blood mononuclear cells (PBMCs) and of proliferating CD4+ T cells. The OB-D secretome significantly promoted the expansion of regulatory CD25+ T cells. Regarding gene expression of MoDCs, remarkably up-regulated mRNA expression of CD209, HLA-DRA, CSF3, IL10 and IL8 was detected when DCs were cultured in the presence of OB+/-D secretomes. At the same time, secretomes seemed to have an impact in the down-regulation of IFNγ and IL12B gene expression. At protein level, OB+/-D secretomes significantly up-regulated IL-10 and IDO (indoleamine-pyrrole 2,3-dioxygenase) levels whereas IL-12/IL-23p40 levels were down-regulated in supernatants of MoDCs when cultured under the presence of OB+/-D secretomes. Taken together, while secretomes from untreated JPCs had only little effects on the process of maturation of MoDCs, secretomes derived from osteogenically induced JPCs were able to inhibit the phenotypic and functional maturation of MoDCs.